A critical study on the right to life of foetus in Malaysia / Nurul Ainaa Syaiirah Mohd Hanafiah … [et al.] - Mohd Hanafiah, Nurul Ainaa Syaiirah; Nik Muhammad, Nik Muizzuddin; Paisol, Nadhira Hanna; Kamaruddin, Syarafina Diana (2011)
A foetus life has been endangered due to the act of the mother taking drugs and alcohol during pregnancy, criminal violence, abortion and toxic exposure. Federal Constitution of Malaysia does not considered a fetus as person and United Nation Convention on the Rights of Child 1989, only recognizes the legal protection of child after birth. There is a need to establish legislation as there is only provisions on abortion and miscarriage in Malaysian Penal Code but not protection for a foetus life with regards to the misconduct of the mother that used drugs or alcohol during pregnancy and criminal violence. Comparing to the United State of America, Malaysia does not give much attention to the right to life of a foetus in the womb. Thus, this would prevent any punishment towards the mother that neglecting their baby. Due to this, the possibility of adopting the USA's foetal protection policy with regards to the right to life for a foetus into Malaysian law must be taken seriously. The implementation, effectiveness, reception of the USA legislation in Malaysia will be used to provide a solid ground of this research. This research involves qualitative research, library based research and also semi structured interviews. This research is only focus on misconduct of the mother, criminal violence and toxic exposure towards the mother. This research research is to assist the law making authority to improve the existing law regarding the rights of fetus to be effective as in USA.